Heat, cold, and environmental emergencies in athletes - Sidhar, K.; Elliott, K.; Ibrahem, M. (Clinics in Sports Medicine, 2023)
Understand cold-related illness and recognize emergent management indications for frostbite, hypothermia, and nonfreezing injuries.